Studies on the political economy, society and culture of Latin America and the Caribbean. Democracy and development in Latin America / Louis Lefeber, Liisa I. North - Lefeber, Louis [et.al] (Estados Unidos de America: CERLAC, 1980)
Democracy and development in Latin America, the dynamics of peripheral capitalism, notes on the international economic crisis of the seventies and the developing countries, Latin América and the world economy, production relations and the third world, spatial population distribution, urban and rural development, technology choice and technological change in agriculture, the case of Colombia, development policies and demographic change in socialist Cuba, education and culture in a disciplinary society, Canada and Latin America, four points of view.
Table of contents, graph
Col. Soc
Keywords: 1. SOCIALISM-MARXISTA 2. DEMOCRACY-DEVELOPMENT-LATIN AMERICA 3. SOCIAL CHANGE 4. CAMBIO SOCIAL 5. SOCIOLOGY